Regards philosophiques sur la question de la démarcation entre science et non-science aujourd’hui - Stéphanie Ruphy (Recherches en Éducation)
The issues of the demarcation between science and non science are significantly renewed in our contemporary societies, which put science and technological innovation at the center of their development. Which resources are offered today by philosophy of science to think this demarcation and propose operational criteria of demarcation? This article presents some of the main recent relevant philosophical propositions, which acknowledge both the shortcomings of the traditional epistemological criteria proposed last century and the abandonment of unitary view of science that used to go hand in hand with these criteria.